2014
DOI: 10.1089/fpd.2013.1732
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation ofCampylobacter jejuniwith Dielectric Barrier Discharge Plasma Using Air and Nitrogen Gases

Abstract: Air and nitrogen gas are commonly used feed gases for plasma generation and are economically useful in industrial applications. The two gases were compared in dielectric barrier discharge plasma for the inactivation of Campylobacter jejuni on an agar surface. Plasma treatment with nitrogen gas for 20 s did not yield any reduction (p>0.05) in viable cell count. However, a 0.8-log reduction (p<0.05) in colony-forming units (CFU) occurred when the nitrogen gas was supplemented with 2% (vol/vol) air. The use of ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…In spite of the cell disruption and the loss of bacterial viability, the thickness of P. aeruginosa biofilm was also significantly reduced post the DBD exposure [42]. Regarding planktonic cells, the herein presented data find confirmation in the study of Kim et al [43], who reported a bacterial membrane interruption in Campylobacter jejuni based on the BacLight assay after a five-second application of DBD, generated under an oxygen atmosphere, or two minutes of DBD, generated under a nitrogen atmosphere. So far, disorganization of the bacterial membrane post plasma treatment has been attributed to the impact of plasma-generated charged particles, i.e., ions and electrons [44].…”
Section: Mechanism Of the Antibacterial Action Of Dbdsupporting
confidence: 85%
See 1 more Smart Citation
“…In spite of the cell disruption and the loss of bacterial viability, the thickness of P. aeruginosa biofilm was also significantly reduced post the DBD exposure [42]. Regarding planktonic cells, the herein presented data find confirmation in the study of Kim et al [43], who reported a bacterial membrane interruption in Campylobacter jejuni based on the BacLight assay after a five-second application of DBD, generated under an oxygen atmosphere, or two minutes of DBD, generated under a nitrogen atmosphere. So far, disorganization of the bacterial membrane post plasma treatment has been attributed to the impact of plasma-generated charged particles, i.e., ions and electrons [44].…”
Section: Mechanism Of the Antibacterial Action Of Dbdsupporting
confidence: 85%
“…This explains the TEM-visualized release of the inner cytoplasmic contents (Figure 6). Analogous effects of the DBD treatment towards human bacterial pathogens were described previously [36,[40][41][42][43]. For instance, the utilization of CLSM by Ziuzina et al [42] revealed that either the direct or indirect 300 s action of DBD led to the recording of strong propidium iodide-related signals from the plasma-treated biofilms of P. aeruginosa.…”
Section: Mechanism Of the Antibacterial Action Of Dbdmentioning
confidence: 58%
“…Among various plasma techniques, the non-thermal atmospheric dielectric barrier discharge (DBD) may be a most promising one. In fact, non-thermal DBD has been widely applied in inactivation of pathogen 20 21 , chemical synthesis 22 , film deposition 23 , material surface modification 24 and etc. When plasma takes place either over the solution surface or in the solution, a variety of physical and/or chemical processes are initiated.…”
mentioning
confidence: 99%
“…A comparison of air and nitrogen gas in dielectric barrier discharge plasma for the inactivation of Campylobacter jejuni reported that nitrogen gas for 20 s did not yield any reduction (p > 0.05) in viable cell count. However, a 0.8-log reduction (p < 0.05) in colonyforming units (CFU) was observed when the nitrogen gas was supplemented with 2% (vol/vol) air [113]. Shi et al [114] noted that relative humidity, gas type, and treatment time are all significant on generated ozone concentration and aflatoxin degradation.…”
Section: Factors Influencing the Efficacy Of Cold Plasmamentioning
confidence: 99%